Analisis Faktor Faktor yang Mempengaruhi Penggunaan Teknologi Komunikasi pada Pembelajaran Jarak Jauh (Studi Kasus: Mahasiswa Fakultas Ilmu Komputer UB) - Lalu Muhammad Dzuu Mirrotin Nurkholis; Diah Priharsari; Satrio Agung Wicaksono (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
With the presence of COVID-19, the learning system has turned into distance learning. The use of communication technology is one solution to keep the learning process going. The role of communication technology in distance learning can help the communication process between students and teachers. The implementation of this distance learning system makes students get new experiences in the learning process using communication technology. The model used in this study is the Unified Theory of Acceptance and Use of Technology (UTAUT) which explains the behavioral factors of users in accepting technology. UTAUT is also used in various studies to see the intention and behavior of using technology. The purpose of this study is to determine the factors that influence the use and selection of communication technology in distance learning, and to find out how students view communication technology in the distance learning process. Data collection and analysis was carried out qualitatively on students of the Faculty of Computer Science, Universitas Brawijaya by means of interviews and thematic analysis. The results of this study, there are four factors in the use of communication technology, namely performance expectancy, effort expectancy, social expectany, and facilitating conditions. Two factors for choosing communication technology, namely application policy and application performance. Based on the results of the thematic analysis, it was found that communication technology can help students in distance learning.